Integrative analysis of bulk and single-cell RNA sequencing data reveals increased arachidonic acid metabolism in osteoarthritic chondrocytes - Wu, Kan; Zhong, Zhaoqian; Chen, Li; Luo, Haihua; Jiang, Aolin; Tao, Linlin; Jiang, Yong (Frontiers in Medicine, 2025)
BackgroundAbnormal lipid metabolism in chondrocytes, especially arachidonic acid (AA) metabolism, has attracted considerable attention in promoting osteoarthritis (OA) progression. However, the metabolic regulation of chondrocytes in OA remains to be investigated.MethodsBulk RNA sequencing (RNA-seq) data and single-cell RNA sequencing (scRNA-seq) data of human knee cartilage were downloaded from public databases. Gene set variation analysis (GSVA) and weighted correlation network analysis (WGCNA) were used to explore functional regulation and gene expression characterization. A reference gene set from the Kyoto Encyclopedia of Genes and Genomes (KEGG) database was used to validate metabolic changes. CellChat analysis was performed to investigate the communication among osteoarthritic chondrocytes. Human immortalized chondrocytes were stimulated with macrophage migration inhibitory factor (MIF), then quantitative real-time PCR (qPCR) and western blot (WB) analysis were used to detect transcription or translation levels of genes. Enzyme linked immunosorbent assay (ELISA) was used to measure AA content. Cartilage from OA patients was collected for immunohistochemistry (IHC) to validate protein expression.ResultsFunctional analysis revealed significant activation of the AA metabolic pathway was significantly enriched in the cluster of proliferative chondrocytes (ProCs). CellChat analysis indicated that the incoming signals of MIF increased in ProCs, and the expressions of extracellular signal-regulated kinase (ERK) and phospholipase A2 group IVA (PLA2G4A) were upregulated. Moreover, functional analysis showed that the ERK pathway was enriched in ProCs. Cell experiments indicated MIF stimulation elevated phospho-ERK (p-ERK) and PLA2G4A expression and AA content. IHC showed p-ERK and PLA2G4A were significantly activated in OA cartilage. MIF also upregulated interleukin 1β (IL1B) and matrix metalloproteinase 13 (MMP13) expression.ConclusionOur study shows that MIF stimulation of chondrocytes can activate the ERK/PLA2G4A signaling pathway and increase AA production. ProCs located in the proliferative layer of cartilage are likely the main cells executing this mechanism. Therefore, targeting and inhibiting MIF signaling in chondrocytes, especially in ProCs, could be a novel strategy for the prevention and treatment of OA.